2010
DOI: 10.1021/bi1012854
|View full text |Cite
|
Sign up to set email alerts
|

MbtH-Like Proteins as Integral Components of Bacterial Nonribosomal Peptide Synthetases

Abstract: The biosynthesis of many natural products of clinical interest involves large, multi-domain enzymes called nonribosomal peptide synthetases (NRPSs). In bacteria, many of the gene clusters coding for NRPSs also code for a member of the MbtH-like protein superfamily, which are small proteins of unknown function. Using MbtH-like proteins from three separate NRPS systems, we show that these proteins co-purify together with the NRPSs and influence amino acid activation. As a consequence, MbtH-like proteins are inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
196
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(208 citation statements)
references
References 14 publications
11
196
0
1
Order By: Relevance
“…Felnagle et al (6) have shown that purified YbdZ can activate adenylating enzymes of different NRPSs, albeit with low efficiency. To exclude the possibility that YbdZ would copurify with the expressed adenylating enzymes and interfere with subsequent investigations, we deleted the ybdZ gene from the E. coli expression host utilizing the same Red/ET-mediated recombination strategy as described in a previous study of our group (11).…”
Section: Expression and Purification Of Tyrosine-adenylating Enzymes mentioning
confidence: 99%
See 3 more Smart Citations
“…Felnagle et al (6) have shown that purified YbdZ can activate adenylating enzymes of different NRPSs, albeit with low efficiency. To exclude the possibility that YbdZ would copurify with the expressed adenylating enzymes and interfere with subsequent investigations, we deleted the ybdZ gene from the E. coli expression host utilizing the same Red/ET-mediated recombination strategy as described in a previous study of our group (11).…”
Section: Expression and Purification Of Tyrosine-adenylating Enzymes mentioning
confidence: 99%
“…Coexpression of CloH and CloY-Felnagle et al (6) reported previously that the adenylating enzymes CmnO and VioO showed moderate activity upon addition of the MbtH-like proteins CmnN and VioN. However, much higher activity could be obtained when CmnO or VioO (as N-terminally His-tagged proteins) was expressed simultaneously with CmnN or VioN (as untagged proteins), followed by copurification of the proteins in the form of the resulting complexes.…”
Section: Tyrosine-activating Enzyme Novh Is Active In the Absence Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Siroheme-dependent sulfite reductase (Rv2391) was hence solubly produced by coproducing uroporphyrinogen III C-methyl-transferase (Rv2847c) (56). Similarly, nonribosomal peptide synthetases, MbtE and MbtF of mycobactin biosynthesis, were solubly produced only by co-producing 8 kDa MbtH with a previously unknown role in the pathway (57,58). Yet another strategy of obtaining structural data for difficult or insoluble Mtb proteins is to replace them with mycobacterial orthologues.…”
Section: Smegmatis MC 2 4517mentioning
confidence: 99%